ANALISA POLA PERGERAKAN SESAR SUMATRA BERDASARKAN PENGAMATAN DATA GPS 2016-2017 GUNA MENGETAHUI AKTIVITAS SEISMIK (JURNAL SPASIAL, 2019)
Sumatran fault is one of active seismogenic zones on the earth that required a seismic activity movement monitoring for Sumatra Fault System (SSS) observation  patterns. GPS observation study was carried out to fit a monitor along the fault that patterns movement can be detected from time series calculation shows by coordinates displacement for outer and volcanic arc ridge areas. Two types of observation stations used, namely Sumatran GPS Array (SuGAr) and  Continuously Operating Reference Station of  Geospatial Information Agency (CGPS BIG). seventeen (17) observation SuGAr data stations produce velocity vectors that vary from 14.5 mm / year to 48.7 mm / year in the east to west direction and -9.2 mm / year to 37.4 mm / year in the North South direction. On BIG CGPS stations using 4 observation stations with the calculation of velocity vector ranging from 25.6 mm / year to 31.7 mm / year in the east to west direction and 5.2 mm / year to 15.4 mm / year in the direction North South. Movement pattern also indicated that the area has a rotation movement and locking.    Sesar Sumatra merupakan zona aktif seismogenik di bumi yang membutuhkan monitoring pergerakan aktivitas seismik untuk pengamatan pola pergerakan Sumatra Fault System (SSS). Studi pengamatan GPS merupakan metode monitoring yang sangat cocok untuk diterapkan di sepanjang sesar tersebut sehingga pola pergerakan dapat dideteksi dari kalkulasi deret waktu yang ditunjukkan oleh pergeseran koordinat dari pola pergerakan daerah sesar seperti daerah outer arc ridge dan volcanic arc ridge. Dua jenis data pengamatan digunakan yaitu data Sumatran GPS Array (SuGAr) dan Continuously Operating Reference Station Badan Informasi Geospasial (CORS BIG). 17 data pengamatan dari stasiun SuGAr menghasilkan vektor kecepatan yang bervariasi antara 14,5 mm/tahun hingga 48,7 mm/tahun pada arah timur ke barat dan -9,2 mm/tahun hingga 37,4 mm/tahun pada arah utara selatan. Stasiun CORS BIG dengan 4 titik pengamatan menghasilkan perhitungan vektor kecepatan antara 25,6 mm/tahun hingga 31,7 mm/tahun pada arah timur ke barat dengan 5,2 mm/tahun hingga 15,4 mm/tahun pada arah utara selatan. Pola pergerakan juga menunjukan adanya pergerakan rotasi dan locking.